Estimating the immunogenicity of blood group antigens: a modified calculation that corrects for transfusion exposures. (24th June 2016) - Stack, Gary; Tormey, Christopher A.
Summary: Calculations of blood group antigen immunogenicity have been based on antigen and antibody frequencies in transfused populations, with the assumption of a single red blood cell (RBC) unit exposure per patient. Given that patients are usually transfused >1 RBC unit, antigen exposures will be greater than assumed, resulting in inaccurate immunogenicity calculations. As such, the goal of this study was to modify the calculation to correct for RBC exposures. To further improve accuracy, we used an empirically‐derived immunogenicity for the reference antigen, K, in calculations of absolute immunogencity and eliminated anamnestic and pre‐existing antibodies (i.e., antibodies induced outside the study site) from the calculation. Alloantibody numbers for the top 12 specificities and mean RBCs (MRBC) transfused per patient were obtained from the records of a hospital transfusion service. A revised immunogenicity calculation, incorporating a correction for MRBC, was developed. This correction resulted in up to a 4‐fold increase in the immunogenicity of relatively high frequency antigens, with smaller increases for lower frequency antigens, yielding the following revised immunogenicity ranking: K>Jk a >Lu a >E>P1>c>M>Le b >C>Le a >Fy a >S. Use of an empirical value for K immunogenicity resulted in a 1·9‐fold increase in absolute immunogenicities for all antigens. In summary, the calculation of blood group antigen immunogenicity has been further refined.